Evaluation of Hepatoprotective Effect of a Polyherbal Megakutki against Paracetamol-Induced Hepatotoxicity - Giri, Asha Elizabeth; Rao, Vanishree; Singhal, Sandeep; Gourishetti, Karthik; Biswas, Subhankar; Nandakumar, Krishnadas; Chamllamudi, Mallikarjuna Rao; Dave, Jeetesh; Dave, Rakesh; Sumalatha, Suhani; Kumar, Nitesh (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Megakutki® (MK) is a polyherbal preparation of 11 standardized extracts that are individually proven for hepatoprotection scientifically. Aim: Study evaluated MK’s hepatoprotective potential against paracetamol (PCM) in in-vitro on Hep G2 cells using cell viability, cell cycle analysis and apoptotic studies and in in-vivo in Wistar rats using liver function tests, histological and DNA fragmentation study. Materials and Methods: In in-vitro studies, IC50 (50% inhibition in viability) values of silymarin, MK and PCM were found out by MTT assay. In-vitro hepatoprotection was found out by pretreating the cells with below-IC50 concentrations of MK and silymarin for 24h followed by PCM (at IC50 concentration) challenge for next 24h and % viability was evaluated using MTT assay. Same treatment protocol was followed for cell cycle analysis and apoptotic studies (100 and 200 μg/ml for MK and 50 μg/ml for silymarin and 40μM for PCM). In in-vivo study, animals were grouped in six, namely, vehicle, PCM control, silymarin (50 mg/kg, standard), MK (100 and 300 mg/kg) groups. Animals were dosed for 8 days while they were challenged on day 6 (except vehicle group) with PCM (2.75 g/kg p.o). On day 8, blood and livers were collected under anaesthesia and analyzed. Results: In-vitro results showed hepatoprotection by MK and silymarin by inhibition of PCM-induced cell death apoptotic cells percentage. In in-vivo study, MK and silymarin reversed the altered liver function and elevated oxidative stress markers (catalase, SOD, GSH, total thiols and lipid peroxidation) compared to paracetamol alone group. Both MK and silymarin decreased the percentage of DNA fragmentation and histopathological changes in liver tissue compared to the PCM group. Conclusion: The in-vitro and in-vivo studies showed the hepatoprotective effect of MK by the prevention of PCM-induced induction of oxidative stress by its antioxidant potential thereby preventing PCM-induced DNA damage.
Keywords: Megakutki; Paracetamol; Hepatoprotection; Cell viability; Hep G2